The 300 MeV synchrotron at Tomsk Polytechnical Institute - Anokhin V. P.; Vlasov A. G.; Vorobyev А. А. Alexander Akimovich; Eponeshnikov V. N.; Gabrusenko I. L.; Kalinin B. N.; Kositsyn L. G.; Kochegurov V. A. Vladimir Alexandrovich; Kuz'min V. N.; Sipailov G. A.; Solntsev B. A.; Tolmachev V. I.; et al. (1970, 1970)
В фонде НТБ ТПУ отсутствует